PEMBUATAN SISTEM INFORMASI GEOGRAFIS SUMBERDAYA ALAM KABUPATEN KULON PROGO BERBASIS WEB - , BRIGITTA YOLANDA PUSPA PERSADA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Kulon Progo District, Special Region of Yogyakarta is a district that has many diverse of natural resources potential, but the resources have not been used properly by the community. If the community can utilize the natural resources properly, the life of the local community can be more prosperous. This bad utilization of natural resources is caused by some reasons